Equity at the Ballot Box: Health as a Resource for Political Participation Among Low-Income Workers in Two United States Cities - McGuire, Cydney M.; Gollust, Sarah E.; De Marco, Molly; Durfee, Thomas; Wolfson, Julian; Caspi, Caitlin E. (Frontiers in Political Science, 2021)
Objective: The purpose of this study is to identify health resources associated with propensity to vote at the local-level among low-wage workers in two United States. cities. Literature confirms individuals of lower income have a lower propensity of turning out to vote, yet few studies have focused on low-income populations to identify the variation in factors associated with voting within this group. Furthermore, few studies have investigated health and voter turnout at the local-level. In this study, we examine factors related to political participation at the local-level within a low-wage sample, examine mental, physical, behavioral, and social health and their association with voter turnout, and assess if these relationships differ by city. Methods: We use cross-sectional survey data from a sample of 974 low-wage workers in Minneapolis, MN and Raleigh, NC. We computed descriptive statistics and employed a logistic regression to predict their likelihood of local voter turnout, with the key independent variables being health resources, such as self-rated health, body mass index (BMI), mental disability, smoking status, and health insurance status. We employed a logistic regression fully interacted with a city indicator variable to assess if these associations differed by city. Results: In both cities, less than 50 percent of respondents reported voting in the last election for mayor or city council. About three-quarters of the sample reported food or housing insecurity and the majority of respondents reported utilizing some government assistance, such as supplemental nutrition programs. BMI greater than 30 was significantly associated with lower likelihood of voter turnout compared to those of lower BMI status (marginal effect = −0.10, p = 0.026). Never smoking or quitting was significantly associated with higher likelihood of voter turnout compared to those who reported being a current smoker (marginal effect = 0.10, p = 0.002). Those with health insurance were significantly more likely to report voting compared to those without any insurance (marginal effect = 0.10, p = 0.022). These results did not significantly differ by city. Conclusions: Our research suggests low-wage workers face significant health burdens which may impact their propensity to vote at the local-level, and these associations do not significantly vary by city despite demographic and political differences between two jurisdictions.